DYNAMICAL EVOLUTION NEAR-PARABOLIC COMETS TO HALLEY-TYPE ORBITS - Biryukov, E. E. (Одеські астрономічні публікації, 2017)
The capture of comet from the near parabolic flux of the Oort cloud to Halley-type orbits (P < 200 yr, perihelion distanses q < 1,5 AU, and Tisserand parametr T < 2) is investigated Two types of capture into Halley-type orbits are found. We show that probability of capture HTC from the near-parabolic flux has the strong dependence on Galactic perturbation. We also show the essential influence of secular perturbations on dynamical evolution of comets in planetary region.